Wealth-based inequalities in tuberculosis prevalence among households having children and young adults in India: insights from Indian demographic and health surveys (2015–2021) - Saurabh Singh; Quazi Syed Zahiruddin; Sorabh Lakhanpal; Suhas Ballal; Sanjay Kumar; Mahakshit Bhat; Shilpa Sharma; M Ravi Kumar; Yogesh Kumar Dhandh; Sarvesh Rustagi; Mohammed Alissa; Muhammad A. Halwani; et al. (BMC Infectious Diseases)
Abstract Background Tuberculosis (TB) remains a significant health concern in India, especially among households with children and young adolescents aged 6–17 years. Despite ongoing research, there is a knowledge gap regarding specific risk factors for TB within this demographic. This study aims to bridge this gap by examining the association between TB and various socio-demographic factors, including socioeconomic status, nutritional status, and environmental conditions. Data and methods Utilizing data from the National Family Health Survey (NFHS) 4th and 5th round (2015-16 and 2019-21), this study conducted a comprehensive cross-sectional analysis. Unadjusted and Adjusted Logistic regression is utilized to identify key factors influencing TB. Furthermore, Wagstaff decomposition analysis is applied, to quantifying the factors that contributes to the inequalities in social determinants on the wealth-related inequality observed in the prevalence of TB. Results The study observed a notable decline in TB prevalence from 1.7 to 1.2% among individuals from households having children and young adolescents aged 6–17 years. Additionally, factors like the use of unclean cooking fuel, lack of electricity, and unimproved toilet facilities were associated with increased TB prevalence. Wealth-based inequality in TB prevalence was also evident, with the burden falling disproportionately on poorer households. Unclean fuel is the most significant determinant of wealth-based inequality in TB, contributing to nearly 2/5th (18.5% in NFHS-4) of the observed inequality. Notably, gender did not significantly influence TB prevalence. Conclusion The decline in TB prevalence in India correlates with improvements in socio-economic and living conditions, as evidenced by increased access to better housing, clean fuel, and sanitation facilities. The study underscores the need for integrated public health strategies that address both medical and socio-environmental determinants of TB. Improving socio-economic conditions, alongside targeted healthcare interventions, appears vital in reducing the TB burden in high-prevalence settings like India. This research emphasizes the importance of comprehensive approaches to combat pediatric TB, combining clinical care with enhancements in living standards and access to basic amenities.